Stability Analysis of Mass Transfer on a Continuous Flat Plate Moving in Parallel or Reversely to a Free Stream in the Presence of Chemical Reaction by Haar Wavelets - Vishwanath Awati; N. Mahesh Kumar; Akash Goravar (Journal of Applied and Computational Mechanics)
This study investigates two-dimensional viscous incompressible boundary layer flow involving mass transfer above an uninterrupted flat surface in the presence of chemical reaction. Applicable similarity transformations, transform the leading equations into a system of nonlinear ordinary differential equations. These equations are solved via collocation approach using Haar wavelets. The double solutions exist and are presented through graphs. The obtained solutions are confirmed by comparing them with earlier findings. The various physical quantities are enfolded and convinced carefully using numerical and theoretical approaches. Enhancement in Schmidt number increases the mass transfer rate for upper branch solution and reduces for lower branch solution. Mass immersion arises for constructive chemical reaction and mass transfer enhances for destructive chemical reaction. Finally, the stability analysis is performed.